Avascular Necrosis of the Talus After Subchondroplasty. (September 2021) - Hanselman, Andrew E.; Cody, Elizabeth A.; Easley, Mark E.; Adams, Samuel B.; Parekh, Selene G.
Background: Subchondroplasty (SCP) is a relatively new procedure, developed in 2007 for the treatment of bone marrow lesions (BMLs), that has shown promising results in the knee through several different case series. The foot and ankle literature, however, is sparse, with only a few documented case reports or case series. At our institution, we have identified several patients with complications after this specific procedure. As a result, we report our case series of patients who developed talar avascular necrosis (AVN) after undergoing SCP. Methods: A retrospective review was performed of patients who underwent SCP for a talar BML at our facility or who were referred to our facility after undergoing SCP at an outside institution. Patients were included if they developed radiographic evidence of talar AVN after the procedure. Patient demographics, comorbidities, concomitant intraoperative procedures, complications, and subsequent interventions were reviewed. Results: Seven patients were identified as having radiographic evidence of talar AVN after SCP. Average time interval was 23 months postoperative from index procedure to radiographic confirmation of AVN. Two of the index procedures were performed at our institution, whereas 5 of the index procedures were performed at outside institutions and referred for further management. Three patients had documented risk factors for AVN before the SCP procedure. All 7 patients were symptomatic from the AVN. Conclusion: We identified 7 patients who went on to develop talar AVN after having undergone SCP. Level of Evidence: Level IV, case series.